Perspective Insights into Disease Progression, Diagnostics, and Therapeutic Approaches in Alzheimer's Disease: A Judicious Update - Jan, Arif Tasleem; Azam, Mudsser; Rahman, Safikur; Almigeiti, Angham M. S.; Choi, Duk Hwan; Lee, Eun Ju; Haq, Qazi Mohd Rizwanul; Choi, Inho (Frontiers in Aging Neuroscience, 2017)
Alzheimer’s disease (AD) is a neurodegenerative disorder that characterized by the progressive accumulation of β-amyloid fibrils and abnormal tau proteinsin and outside of neurons. Representing a common form of dementia, aggravation of AD with age increasesthe morbidity rate among the elderly.Although mutations in the ApoE4act as potent risk factors for sporadic AD, familial AD arises through malfunctioning of APP, PSEN-1 and-2 genes.AD progresses through accumulationof amyloid plaques (Aβ) and neurofibrillary tangles (NFTs) in brain, which interfere with neuronal communication. Cellular stress that arises through mitochondrial dysfunction, endoplasmic reticulum malfunction, and autophagy contributes significantly to the pathogenesis of AD.With high accuracy indisease diagnostics, Aβ deposition and phosphorylated tau (p-tau) are useful core biomarkers in the cerebrospinal fluid (CSF) of AD patients. Although five drugs are approved for treatment in AD, their failures in achieving complete disease cure has shifted studies toward a series of molecules capable of acting against Aβ and p-tau. Failure of biologics or compounds to cross the blood-brain barrier (BBB) in most cases advocates development of an efficient drug delivery system. Though liposomes and polymeric nanoparticles are widely adopted for drug delivery modules, their use in delivering drugs across the BBB has been overtaken by exosomes, owing totheir promising results in reducing diseaseprogression.